A Clinicopathological and Immunohistochemical Correlation in Cutaneous Metastases from Internal Malignancies: A Five-Year Study. (25th August 2014) - Nibhoria, Sarita; Tiwana, Kanwardeep Kaur; Kaur, Manmeet; Kumar, Sumir
Abstract : Cutaneous metastases from internal malignancies are uncommon and occur in 0.6%–10.4% of all patients with cancer. In most cases, cutaneous metastases develop after the initial diagnosis of the primary internal malignancy and late in the course of the disease. Skin tumors are infrequent in Asian population and cutaneous metastases are quite rare. Cutaneous metastases carry a poor prognosis with average survival of few months. In the present five-year study 1924 malignant tumors were screened which included only nine cases of cutaneous metastatic deposits. A wide range of site and clinical presentations including nodules, plaques, and ulcers was noted. Histopathological findings were significant and corresponded with the primary internal malignancy. Cutaneous metastases from breast carcinoma (44.4%) were the most common finding followed by non-Hodgkin lymphoma and renal cell carcinoma (22.2% each) and carcinoma cervix (11.1%). The aim of our study is to classify the cutaneous metastases and to evaluate their clinicopathologic and immunohistochemical correlation with the primary tumor.